Kekuatan Mengikat Risalah Lelang Bagi Pembeli Lelang Terhadap Hak Tanggungan Bagi Pembeli Lelang di Kantor Pelayanan Kekayaan Negara dan Lelang (Kpknl) Kota Batam - Andi Putra Pratama, Guswanda; Respationo, Soerya; Erniyanti, Erniyanti; Fadlan, Fadlan; Nofrial, Ramon (UNES Law Review, 2023)
This research aims to determine the obstacles that occur for auction buyers in vacating auction objects due to resistance from debtors or third parties, denying that debtors have been negligent in carrying out their obligations towards creditors, debtors who do not acknowledge the amount of debt from all costs that have been incurred by creditors first for the purposes of encumbrances in mortgage rights. The nature of this research is analytical descriptive. This research is also included in empirical juridical research. The data source used in this research is secondary data sources. This research was carried out at the Batam State Property and Auction Service Office (KPKNL) which was the research location. In collecting data for this research, the techniques used were library research and field research methods. The data collection tools used in this research are document study or literature study and interviews. Meanwhile, the data analysis used in this research is qualitative analysis. The conclusions that will be drawn in this research are carried out deductively. The results that have been obtained from this research are the auction minutes as authentic deeds that have perfect evidentiary power, the efforts made by KPKNL in overcoming obstacles in the auction for the execution of mortgage rights at KPKNL must be completed properly and auction buyers who have good intentions must be protected by law.